1991
DOI: 10.1152/ajpendo.1991.260.6.e897
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of chloroquine in patients with non-insulin-dependent diabetes mellitus

Abstract: Clinical studies have demonstrated that chloroquine and hydroxychloroquine improve glucose metabolism in patients with insulin-resistant diabetes mellitus. The mechanism of action has not been determined. We undertook a randomized double-blind placebo-controlled trial of 3 days of oral chloroquine phosphate, 250 mg four times daily, in 20 patients with non-insulin-dependent diabetes mellitus controlled by diet. Rates of glucose appearance (Ra) and disappearance (Rd) were evaluated by infusion of stable isotopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 25 publications
0
48
0
2
Order By: Relevance
“…This would suggest that inhibition of autophagy or other lysosomal functions may turn out to be beneficial, probably due to inhibition of hepatic insulin degradation [101] or, as more recently proposed, by inhibiting lysosome-dependent lipolysis in adipose tissue macrophages [11].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 87%
“…This would suggest that inhibition of autophagy or other lysosomal functions may turn out to be beneficial, probably due to inhibition of hepatic insulin degradation [101] or, as more recently proposed, by inhibiting lysosome-dependent lipolysis in adipose tissue macrophages [11].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 87%
“…A few small randomized controlled trials showed that HCQ lowers HbA 1c and LDL cholesterol levels in patients with type 2 diabetes (106-110). The mechanisms of hypoglycemia with HCQ are inferred from studies of the parent drug, chloroquine, which has been shown to increase insulin levels in man by both increasing insulin secretion and inhibiting its degradation (111 It also remains a challenge to adequately assess inflammation in man, since crude surrogate markers are being used, and it is currently difficult to appreciate tissuespecific variations in the level and type of inflammation. Preclinical studies in animal models are most helpful in this regard; however, it may be difficult to extrapolate from findings in animal models to the clinical setting.…”
Section: Salsalatementioning
confidence: 99%
“…We employed immunoblotting to assess the extent of phosphorylation at Ser 21 and Ser 9 of GSK-3␣ and GSK-3␤, respectively, as a measure of insulin-induced GSK-3 inactivation. In parallel with our observations on PI 3-kinase and Akt, bafilomycin did not affect GSK-3 serine phosphorylation at 2 min after insulin but inhibited it by 20% (p Ͻ 0.05 versus insulin alone) at 15 after insulin (Fig.…”
Section: Figmentioning
confidence: 99%